Design of Tambak Lorok Septage Treatment Plant (STP), Semarang City - Merylla Riani, Brigitta
Tambak Lorok of Sewage Treatment Plant (STP) is one of wastewater treatment facility in Semarang City. The volume of sludge entering the STP every day is 41 m3 and the existing service coverage is only 4%.. The existance of STP is very necessary because almost three quarters of the population of Semarang City is served by on-site sanitation system. The treatment plant has not been able to reduce the pollution load contained in the septic sludge maximally. Existing processing efficiency is only about 20-30% of what should be able to reach 90-95% with a stabilization pond system. This condition can be seen from the effluent’s quality that produced at the end of treatment can not meet the standard of domestic wastewater quality based on the Regulation of the Minister of Environment and Forestry No.68/Menlhk/Setjen/Kum/I/8/2016. Some of these parameters which dissatisfy are Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), dan Total Suspended Solid (TSS). Based on that three parameters, can be used to redesign STP to increase the treatment process. In particular, it is necessary to increase the efficiency of suspended solids. Based on the results of laboratory analysis it was found that TSS concentrations still reached 1000 mg / L at the end of processing from those set by the standard of 30 mg / L. Based on the existing conditions, Tambak Lorok STP does not have a sludge separation unit so the TSS concentration in the effluent is still high. In addition, STP doesn’t have the sludge dewatering unit. Sludge as a residual processing from the stabilization pond is only dried on open land without a drainage system so that the liquid coming from the mud will flow directly to the water body. This condition causes the quality of the water body to become more polluted. Therefore, the proposed development plan is the construction of a sludge separation unit (sludge thickener) to be placed at the beginning of processing and a sludge dewatering unit. Alternative selection is done by analyzing several parameters related to existing conditions. These parameters are land requirements, processing efficiency, and ease of operation and maintenance. Based on the results of the analysis of the three parameters, the alternative development plan chosen is Solid Separation Chamber as a sludge separation unit and Sludge Drying Beds as a sludge dewatering unit. The planned development of the STP is planned to be carried out in stages while still considering the volume of stool entering in the coming year will increase along with population growth. The development will be divided into 2 periods with increased service coverage in each period. Period 1, namely in 2021-2030 with a 50% service coverage plan. Whereas period 2, namely in the year 2031-2040 with the plan of service coverage to be 60%. The improvement of this service coverage plan is also based on the Semarang City Wastewater Master Plan. The function of STP as a sludge treatment facility depends on the volume of sludge entering. Therefore, the septic tank desludging system is planned to implement the LLTT (Scheduled Sludge Service System), where the feces truck will periodically suck up household septic tanks according to the schedule. Thus it can be ascertained that there is sludge which is transported to the ITB to be processed. Based on the analysis of operational calculations, the contributions that must be paid by residents in this LLTT system is Rp. 8.000 / KK every month.